PEMBUATAN MIKROKAPSUL MINYAK ATSIRI KULIT KAYU MANIS (Cinnamomun burmanii Bl.) MENGGUNAKAN KOMBINASI GUM ARAB-MALTODEKSTRIN SEBAGAI ENKAPSULAN - BAMBANG KUNARTO (JURNAL LITBANG PROVINSI JAWA TENGAH, 2005)
Cinnamon bark (Cinnamumun burmanii Bl.) is a potential source of flavour, antioxidant and anti fungus in food. Microencapsulation of cinnamon bark oil is to make easier application in food. Microencapsulation is a technology of packaging a solid. liquid or gaseous material in miniature, sealed capsules, that can release their content at such control ling rates under specific conditions. The aim of this research was to seek the best formula of cinnamon bark oil microcapsule. with incomparable combination of arabic gum-maltodextrin as encapsulant. The research experiment arranged in completely randomized design with three replications. The treatments were Fl (one parts of cinnamon bark oil and five parts ofarabic gum and rnaltodextrin ( I 00:0)), F2 (one parts of cinnamon bark oil and five part of arabic gum and maltodextrin (75:25)), F3 (one parts of cinna mon bark oil and five part of arabic gum and maltodextrin (50: 50)), F4 (one parts of cinnamon bark oil and five part ofarabic gum and rnaltodextrin (25:75)) and F5 (one parts of cinnamon bark oil and five part of arabic gum and rnaltodexrrin (0: 100)). The result showed that one part of cinnamon bark oil and five part ofarabic gum and maltodextrin (50:50) had given the best rendement (74.546%). While cinnamon bark oil in capsule 93,89%, cinnamon bark oil in capsule surface 6, l 0%, water content 7,0 I%, wettabiliy I 0, 13 mn and angle of repose 46,530